Use of seismic techniques to evaluate rock mass quality for excavatability assessment - Seman, M.; Kramadibrata, S.; Urosevic, Milovan; Jones, O. (2018)
© 1994 SEG Annual Meeting. All Rights Reserved. Geophysics is often used to estimate the hardness of material to be excavated in mining. In these experiments, different seismic methods were used to determine velocities, from which a rock quality index may be derived. It was concluded that the 'uphole' method is applicable in the excavation mining environment, having the distinct advantage of simplicity.